Persuasive Appeals Construction in Government Tourism ‎Instagram Posts - Eka Dyah Puspita Sari; Mia Agustina; Dian Adiarti; Ririn Trisnawati; Rodey bin Hamzah (JPI: Jurnal Pustaka Indonesia, 2026)
Instagram serves as an excellent tool for tourism marketing. This applies for public institutions that try to brand tourism destinations through the multimodal elements that Instagram provides. This study analyzes the persuasive appeals in the first ten posts on Instagram's official Cilacap tourism account, @wisatabahari.clp. It is a qualitative case study that examines the rhetorical appeals of Aristotle as they are presented in both the text and the images. The data shows that the three rhetorical appeals are present jointly but may serve different roles in different posts. Ethos is achieved through the account's control, the government logos and representations, and the government tourism activities. Pathos, in contrast, is apparent in images of the sea in Cilacap, tourists and participants, cultural and ceremonial activities, and captions with evaluative descriptions of the activity that promote a sense of enjoyment and pride in Cilacap. Logos is present in the operational details provided, such as tickets, opening hours, contact details, and how to get there. Instead of showing the outcome of the appeals to actual audiences, the data shows the implications and presence of governmental/institutional ethos combined with persuasive and visual practical logic. The study shows that a government/institutional Instagram account used specifically to promote tourism has multiple persuasive rational elements and describes an Instagram account's posts in the digital tourism promotional marketing context.